The Mechanical Properties of a Water Hyacinth/Rice Husk Powders Composite for Tissue Engineering Applications - Nasmi Herlina Sari; Suteja Suteja; Yusuf Akhyar Sutaryono (Journal of Fibers and Polymer Composites, 2023)
In this study, composites made from water hyacinth powder (WPH) and rice husk powder (RH) were created using the hot press method, and the composites were characterized to determine their suitability for biomedical applications such as tissue engineering. The mixing ratio of WPH/RH was investigated. Fourier transmission infrared spectroscopy (FTIR) revealed the presence of chemical bonds in the composites under investigation. Tensile tests were used to investigate the mechanical properties of the composite, which revealed that adding water WPH to the rice husk composite reduced the composite's strength. A composite with a 5% WPH content had the highest tensile strength of 32.72 MPa. Meanwhile, the mechanical strength of the other composites studied ranged from 25,537 MPa to 29.43 MPa. However, the elastic modulus of the composite increased with the addition of WPH. The SEM image shows that the powder distribution is less even, the interface between WPH-RH and polyester is quite tight, and the composite contains a number of voids. Characterization of the developed composite demonstrates that the WPH/RH addition ratio can be adjusted to achieve the desired composite properties for tissue engineering and cartilage regeneration applications.